Dependence on composition of electronic properties and stability of Pt-Fe/C catalysts for oxygen reduction - Malheiro, A. R. [UNESP]; Perez, J. [UNESP]; Villullas, Hebe de Las Mercedes [UNESP] (Elsevier B.V., 2010)
This work presents studies of electronic characteristics and alloy stability carried out for Pt-Fe/C catalysts of different compositions (10-50% Fe, in atoms) and same particle size. The electronic properties are characterized by in situ dispersive X-ray absorption spectroscopy (DXAS). The results show a steady decrease in Pt d-band occupancy as the amount of Fe in the alloy increases. The alloy stability is evaluated by prolonged potential cycling up to 1.0 V. Catalysts with Fe content up to 30% show good stabilities and keep their activities for oxygen reduction after prolonged cycling. In contrast, catalysts with Fe content above 30% suffer pronounced Fe leaching. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Pt-based electrocatalyst; Bimetallic nanoparticles; Catalyst stability; Oxygen reduction; Nanostructured cathode materials